Pengaruh Tingkat Kemiskinan, Pengangguran, dan Upah Minimum Terhadap Kesejahteraan Masyarakat di Provinsi Kalimantan Selatan Tahun 2013-2021 - Huda, Nurul; Sa'roni, Chairul (PPJP ULM, 2024)
This research is a quantitative research goals were finding out and analizing the influence of poverty level, unemployment and minimum wages toward citizen welfare in South Kalimantan Province. The analizing technique used is panel data regression with the selected model, namely the Random Effect Model, combining data for 2013-2021 and cross-section data from 13 Regencies/Cities of South Kalimantan Province The data that has been obtained furthermore are analyzed by panel data regression equation analysis using the E-Views 10 Software program. This research results that poverty level, unemployment and minimum wages simultaneously had significant influences toward the welfare of South Kalimantan Province during 2013-2021. Therefore, partial analysis of the poverty level and unemployment is negatively related and not significantly correlate toward citizen welfare in South Kalimantan Province. Minimum wages positively correlated by partial and had significant effect toward citizen welfare in South Kalimantan Province.